International Tourists’ Perception and Behavior towards Government’s Beach Clean-up Policy: A Case Study of Patong Beach, Phuket - KORKAMNERTKAWIN, PATTAMA; PROMSIVAPALLOP, PORNPISANU (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2016)
The purpose of this study is to explore the perceptions of international tourists towards the government’s beach clean-up policy at Patong Beach, Phuket. Specifically, it seeks to examine the relationships between international tourists’ perceptions, their beach-use behavior and their satisfaction of Patong Beach after the government’s beach clean-up policy was implemented. The results of the study were drawn from 389 international tourists who have visited Patong Beach since the implementation of this policy. One-way ANOVA and the Pearson Correlation Coefficient were employed to test the hypotheses. The findings suggested that there were significant differences in international tourists’ perceptions of the policy and their beach use behaviors. Ultimately, practical implications towards beach management and policy implementation were also discussed.